(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The methodological approaches for assessing the financial condition of enterprises in the economic transformation are considered in the article. The ratios, which are calculated on the basis of the financial statements and other accounting information, are allocated among the typical indicators of financial analysis of the company: indicators characterizing the degree of use of loan capital; liquidity; rates of return; indicators of market value. Excess of revenues over expenses related not always identify the impact of financial and economic activity. In order to standardize performance indicators of financial and economic activities, simulation it was proposed to use the efficiency index of financial and economic activity as an integrated indicator of the amount, operating income per unit operating costs; financial results from operations per unit cost of goods; social benefits accrued income per unit of employees; financial results from operations per unit of environmental costs; financial result before taxation per unit of net sales. It was used the method of fuzzy sets for evaluation of economic activity on the example of the Rivne region, taking into account the likely impacts on their business in the short term,. The index performance was studied in the context of fuzzy sets subsystems: the state of «marginal inefficiency« state «no performance factor» state of «relative performance» state «sustainable performance» state «optimal performance».